EFISIENSI USAHA DAN NILAI TAMBAH PENGOLAHAN UBI KAYU MENJADI MODIFIED CASSAVA FLOUR (MOCAF) PADA KELOMPOK WANITA TANI MEDAL ASRI, DESA SUKAWANGI KECAMATAN PAMULIHAN KABUPATEN SUMEDANG - Mia Rosmiati; Rijanti Rahaju Maulani; Angga Dwiartama (Fakultas Seni Rupa dan Desain ITB, 2018)
Cassava is a potential commodity as a flour substitute products. Cassava can be used as flour known as mocaf (modified cassava flour). Mocaf is the product of cassava flour processed using the principle of modifying cells of cassava by fermentation. This fermentation process will produce flour which almost resembles the characteristics and qualities of wheat flour. The purpose of this study was to analyze the efficiency of business and added value analysis. The results showed that the value of business efficiency (R/C ratio) of 1,81, which means that these businesses efficiently and profitably (R/C > 1). The ratio of added value amounted to 49.0%, this means that the processing of mocaf provide added value high enough. Total profits earned by the production process (from 200 kg of cassava) were 227,500.00 IDR. Keywords: Cassava, mocaf, business efficiency, added value.